STRATEGI MANAJEMEN RESIKO PADA PROYEK PENGENDALIAN BANJIR DAN ROB SUNGAI LOJI – BANGER PAKET 1 - Perwiranegara, Alamsyah Fatih; Wibowo, Kartono; Mudiyono, Rachmat (Jurnal Teknik Sipil Giratory UPGRIS, 2024)
Risk management in the form of initial mitigation by considering internal and external factors and issues will be able to narrow the gap in making predictions and strategies to accelerate the completion time of work until it is completely completed. The Loji-Banger River Flood and Robo Control Project Package 1 is one of the government's strategic projects which aims to overcome tidal floods on the north coast of Pekalongan City. Risk assessment is carried out in several stages from risk identification to mitigation suggestions to reduce the scale of risk from inherent risk to residual risk which shows that of the 35 variables assessed, all risk factors have decreased on the risk scale, however there are several risk factors that are of particular concern. because the residual risk is still at a moderate level, so very tight controls or control are needed because it could potentially cause a gap in the work acceleration target time, including possible risks due to delays in material delivery (X2), possible risks due to some of the work land not being free (X11 ), possible risks due to the DIPA Budget Refocusing Issue, its influence on cash flow (X18), possible risks due to the influence of the company's financial condition on the project action plan (X19), possible risks due to errors in preparing work sequences or work zoning (X27).